The Influence of COVID-19 Infection on Chinese Peoples’ Negative Mood: The Role of Rumination and Social Support - He, Lingling; Feng, Zhao; Hu, ChunMei; Pan, Qilan (European Journal of Applied Sciences, 2024)
Objective: To investigate the Influence of COVID-19 infection on Chinese peoples’ negative mood and the role of rumination and social support, so as to provide reference for the prevention and control of COVID-19 infection. Study design：Cross-sectional study. Methods: Using convenient sampling, 2200 people participated to complete a questionnaire survey. Results: The peoples’ infection rate of COVID-19 was 91.3%, and 89.7% people were infected once. COVID-19 infection could predict peoples’ negative mood positively. Rumination played a partial mediating role between COVID-19 infection and negative mood. Social support not only moderated the predictive effect of COVID-19 infection on rumination, but also moderated the predictive effect of rumination on negative mood. Conclusion: High levels of social support can reduce the impact of COVID-19 infection on rumination and the impact of rumination on negative mood. The whole society should support people in coping with COVID-19 infection in multiple ways, and this can reduce their rumination and negative mood.